2011
DOI: 10.1002/bio.1311
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles‐based fluorescence enhancement of the terbium–levofloxacin system and its application in pharmaceutical preparations

Abstract: A sensitive fluorescence (FL) technique is proposed for the determination of levofloxacin (LVX). The method is based on the fact that the weak FL signal of the Tb(III)-LVX system is strongly enhanced in the presence of gold nanoparticles. Gold nanoparticles were prepared by the citrate reduction of HAuCl(4) and characterized by transmission electron microscopy (TEM). Levofloxacin and Tb(III) ion form a fluorescence complex in aqueous solution, and its maximum emission wavelength was found at 545 nm. Optimal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Several MEF approaches have been developed for enhanced sensitivity in the detection of various analytes such as levofloxacin (LOD, 0.2 nM), Hg 2+ (LOD, 4.5 nM) and β-galactosidase (LOD, 100 nM). [163][164][165] Although MEF allows for improved sensitivity, the enhancement is usually limited to 10 fold.…”
Section: Metal Enhanced Fluorescencementioning
confidence: 99%
“…Several MEF approaches have been developed for enhanced sensitivity in the detection of various analytes such as levofloxacin (LOD, 0.2 nM), Hg 2+ (LOD, 4.5 nM) and β-galactosidase (LOD, 100 nM). [163][164][165] Although MEF allows for improved sensitivity, the enhancement is usually limited to 10 fold.…”
Section: Metal Enhanced Fluorescencementioning
confidence: 99%
“…There is a drastic increase in fluorescence in microheterogeneous organized media rather than homogenous solutions [90,91]; micellar solutions obtained with anionic surfactants have the role of bringing the reactants together by trapping the energy donor inside the micelle and binding the lanthanide ion to its surface [85], enhancing the stability of the complexes and shielding them from quenchers [91]. The same effect can be obtained by using coordination polymer nanoparticles (CPNPs) [92], coordination polymer nanosheets (CPNSs) [93] or nanoparticles (NPs) [84,[94][95][96][97][98][99]. The source of the electromagnetic radiation necessary to obtain the excited state of the ligand is either the Xe lamp of the spectrofluorometer, or a chemical species in an excited state, such as SO 2 * obtained through a chemical reaction (chemiluminiscence).…”
Section: Quantitative Determination Of Quinolonesmentioning
confidence: 99%
“…In recent years, metal nanoparticles have been introduced in lanthanides luminescence measurements as surface enhancers that can amplify and improve their luminescence (24)(25)(26)(27)(28)(29)(30). Lee et al (27) reported the determination of levofloxacin using gold nanoparticles (AgNP)-enhanced fluorescence of the Tblevofloxacin system. Kamruzzaman et al (25) applied AgNPenhanced fluorescence to the sensing of terbium complex for the sensitive determination of fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%